2016
DOI: 10.1007/s00125-016-3897-4
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of insulin DNA in response to proinflammatory cytokines during the progression of autoimmune diabetes in NOD mice

Abstract: Aims/hypothesis Type 1 diabetes is caused by the immunological destruction of pancreatic beta cells. Preclinical and clinical data indicate that there are changes in beta cell function at different stages of the disease, but the fate of beta cells has not been closely studied. We studied how immune factors affect the function and epigenetics of beta cells during disease progression and identified possible triggers of these changes. Methods We studied FACS sorted beta cells and infiltrating lymphocytes from N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
3
55
2
Order By: Relevance
“…Notably, Yang et al [82] demonstrated that islets from subjects with type 2 diabetes showed greater methylation at several CpG sites compared to islets from control subjects, suggesting that β-cells might exhibit increasing methylation of the INS gene with progression of disease states. In agreement with this observation, a recent report by the Herold group [87•] showed that the methylation status of the Ins1/Ins2 gene in the β-cell becomes more methylated with disease progression in the NOD mouse.…”
Section: Differentially Methylated Dna As a Biomarker Of β-Cell Stressupporting
confidence: 76%
“…Notably, Yang et al [82] demonstrated that islets from subjects with type 2 diabetes showed greater methylation at several CpG sites compared to islets from control subjects, suggesting that β-cells might exhibit increasing methylation of the INS gene with progression of disease states. In agreement with this observation, a recent report by the Herold group [87•] showed that the methylation status of the Ins1/Ins2 gene in the β-cell becomes more methylated with disease progression in the NOD mouse.…”
Section: Differentially Methylated Dna As a Biomarker Of β-Cell Stressupporting
confidence: 76%
“…The relatively rapid appearance of the subpopulation most likely reflects epigenetic changes in these cells, but further studies will be needed to address this mechanism. Our previous studies showed that cytokines may cause changes in DNA methyltransferases and Ins1/2 DNA methylation (Rui et al, 2016), and we found increased expression of several inflammatory pathways in Btm cells by RNA-seq, including HMGB1(p = 2.11E00), Cxcl15(p = 1.91E00), and IL-6 (p = 2.18E00), among others. Epigenetic changes in other β cell genes are likely to occur, but further study will be needed to identify these mechanisms.…”
Section: Discussionmentioning
confidence: 50%
“…Dissociated islet cells were stained with FluoZin and tetramethylrhodamine ethyl ester perchlorate (TMRE) to identify viable β cells (Jayaraman, 2011; Rui et al, 2016) and with anti-CD45 monoclonal antibody (mAb) to identify islet infiltrates. Representative β cell profiles showing side scatter (SSC) and forward scatter (FSC) in mice of different ages are shown (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in NOD mice, epigenetic changes are induced in β cells by immune mediators (88). The consequences of these and other alterations may include impaired synthetic function but studies with other mediators of cellular stress raise the possibility that cellular transdifferentiation may account for β cell failure (89, 90).…”
Section: Overview Of Disease Mechanismsmentioning
confidence: 99%